2006
DOI: 10.1080/14764170600717902
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of four hair removal lasers and light sources

Abstract: Although hair removal with commonly used systems is, as expected, highly effective, treatment with light-based devices can cause less pain, yet show efficacy similar to laser systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 4 publications
3
46
1
Order By: Relevance
“…This is in contrast to previous studies, which have shown broadly similar levels of efficacy for hair removal with both alexandrite lasers and intense pulsed light systems. In one of the few reported direct comparisons, Amin and Goldberg [24] compared hair removal from the back or thigh using a GentleLase alexandrite laser, a Palomar Starlux IPL (incorporating two different filter settings) and a Lumenis Lightsheer diode laser and found that there were no significant differences between hair count reduction between the systems. It is possible that the increased rate of facial hair growth, especially in women with PCOS, may amplify differences between the two systems in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to previous studies, which have shown broadly similar levels of efficacy for hair removal with both alexandrite lasers and intense pulsed light systems. In one of the few reported direct comparisons, Amin and Goldberg [24] compared hair removal from the back or thigh using a GentleLase alexandrite laser, a Palomar Starlux IPL (incorporating two different filter settings) and a Lumenis Lightsheer diode laser and found that there were no significant differences between hair count reduction between the systems. It is possible that the increased rate of facial hair growth, especially in women with PCOS, may amplify differences between the two systems in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite using higher fluences on the IPL side than on the alexandrite side: mean fluences of 42 and 30 J/cm 2 were used respectively. Previous studies have found hair reductions using IPL systems to vary between 33% and 80.2%, with the improvement lasting up to 30 months following treatment [19][20][21][22][23][24]. The Lumina IPL resulted in mean hair count reductions of 21% at 1 and 3 months follow-up and 27% at 6 months follow-up.…”
Section: Hair Countsmentioning
confidence: 99%
“…The incidence of side effects was significantly higher after diode laser treatment (P ¼ 0.0001). In a CT, Amin and Goldberg [14] evaluated the efficacy of an IPL device (red filter), an IPL device (yellow filter), a 810 nm diode laser, and a 755 nm alexandrite laser in patients (n ¼ 10) with unwanted hair on the back or thigh. Hair counts at 1, 3, and 6 months after the second treatment showed a significant decrease in hair counts ($50%) for all light devices (no statistical difference).…”
Section: Hair Removalmentioning
confidence: 99%
“…Amin and Goldberg performed a recent comparison study in 2006 comparing the decrease in hair counts with four devices: (1) an IPL with a red filter: Palomar, Starlux RS, 65 J/cm 2 ; (2) an IPL with a yellow filter: Palomar, Starlux Y, 35 J/ cm 2 ; (3) an 810-nm diode laser: Lumenis, Lightsheer, 28 J/cm 2 ; and (4) a 755-nm alexandrite laser: Candela, Gentlelase, 18 J/cm 2 (42). A total of 10 patients were treated twice with each device on the back and hair counts were taken at 1, 3 and 6 months after the final treatment.…”
Section: Comparison Of Laser and Ipl Devicesmentioning
confidence: 99%